(untitled) - HJI Panayi, Christiana (Cambridge, UK, 2013)
Includes bibliographical references and index.; "How does EU law affect Member State corporate tax systems and the cross-border activities of companies? This unique study traces the historical development of EU corporate tax law and provides an in-depth analysis of a number of issues affecting companies, groups of companies and permanent establishments. Existing legislation, soft-law and the case-law of the Court of Justice are examined. The proposed CCCTB Directive and its potential application through enhanced co-operation are also considered. In addition to the tax issues pertaining to direct investment, the author examines the taxation of passive investment income, corporate reorganisations, exit taxes and the restrictive effect of domestic anti-abuse regimes. By doing so, the convergences and divergences arising from the interplay of EU corporate tax law and international tax law, especially the OECD model, are uncovered and highlighted"
Keywords: Corporations -- Taxation -- Law and legislation -- European Union countries.; Liên kết -- Thuế -- Luật và pháp luật -- Các nước liên minh Châu Âu